Anxiety level relationship with sleep quality in Post-COVID-19 patients - Ali Multazam; Rahmad Oky Lukman Prasetyo; Bayu Prastowo (Physical Therapy Journal of Indonesia, 2023)
Background: Coronavirus disease 2019 (COVID-19) is a disease from a virus transmitted through saliva or water droplets that come out of the nose when someone infected with the COVID-19 virus coughs or sneezes. Most people will experience mild to moderate respiratory illness through an infection that attacks. This new virus has not yet found a vaccine or special treatment, so someone infected will most likely recover without special treatment. In this case, it can cause anxiety in humans, resulting in poor sleep quality. Methods: Cross-sectional data analysis observation. With a sample size of 56 responders, this study's population was post-COVID-19 patients from Malang Raya. Data were gathered using the Hamilton Rating Scale for Anxiety (HRS-A) and Pittsburgh Sleep Quality Indeks (PSQI) questionnaires. In this study, anxiety is the independent variable and sleep quality is the dependent variable. Results: According to Spearman's statistical test, anxiety and sleep quality have a p=0.00, r=-0.316 with poor values, indicating a relationship between anxiety levels and sleep quality. Conclusion: There is a link between the level of anxiety and the quality of sleep in patients who have had COVID-19.